2021
DOI: 10.3389/fonc.2021.652081
|View full text |Cite
|
Sign up to set email alerts
|

NGFR Increases the Chemosensitivity of Colorectal Cancer Cells by Enhancing the Apoptotic and Autophagic Effects of 5-fluorouracil via the Activation of S100A9

Abstract: Colorectal cancer (CRC) is currently the third leading cause of cancer-related deaths worldwide, and 5-fluorouracil (5-FU)-based chemotherapies serve as important adjuvant therapies before and after surgery for CRC. However, the efficacy of CRC chemotherapy is limited by chemoresistance, and therefore the discovery of novel markers to indicate chemosensitivity is essential. Nerve growth factor receptor (NGFR), a cell surface receptor, is involved in cell death and survival. Our previous study indicated that NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The increased NGFR induced autophagy to mitigate renal tubular damage caused by proteinuria [42]. NGFR enhanced chemosensitivity of colorectal cancer cells to 5-fluorouracil and increased 5-fluorouracil-induced apoptosis and autophagy [15]. Different cells responded differently to NGFR based on cell type and cell differentiation status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased NGFR induced autophagy to mitigate renal tubular damage caused by proteinuria [42]. NGFR enhanced chemosensitivity of colorectal cancer cells to 5-fluorouracil and increased 5-fluorouracil-induced apoptosis and autophagy [15]. Different cells responded differently to NGFR based on cell type and cell differentiation status.…”
Section: Discussionmentioning
confidence: 99%
“…NGFR plays a role in various biological processes, such as cell proliferation, differentiation and death, scar formation, energy expenditure, and hypoxic response [13]. Further studies have revealed that NGFR regulates cell growth, invasion, metastasis, autophagy, and apoptosis in many tumors [13][14][15]. For example, RSV treatment reduced the histone methyltransferase EZH2 significantly, further led to reactivation of neuroblastoma tumor suppressor genes NGFR, and then triggered cellular apoptosis in N-2a cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer, the protein named PTHrP (encoded by PTHLH) can drive the growth of primary and metastatic tumors in mice (26). In colon cancer, Chen et al indicated that NGFR could act as a tumor suppressor by activating S100A9, thus leading to the enhanced apoptotic and autophagic effects of 5-fluorouracil (27). Huang et al found that the NGFR-FOXP3 positive feedback loop contributes to ICOTINIB resistance in non-small cell lung cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer, Chen et al. indicated that NGFR could act as a tumor suppressor by activating S100A9, thus leading to the enhanced apoptotic and autophagic effects of 5-fluorouracil ( 27 ). Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathway include immune system [69], neutrophil degranulation [70], cytokine signaling in immune system [71], extracellular matrix organization [72], post-translational protein phosphorylation [73], biological oxidations [74], metabolism [75] and metabolism of lipids [76] were responsible for progression of CD. CXCL5 [77], CXCL3 [78], PROK2 [79], CXCR1 [80], PYCR1 [81], OSM (oncostatin M) [82], IL15RA [83], LRG1 [84], LCN2 [85], BATF2 [86], CXCL1 [87], S100A9 [88], IFITM1 [89], MYOF (myoferlin) [90], XBP1 [91], MMP3 [92], TAP1 [93], FPR2 [94], CXCL6 [95], C2CD4A [96], IFITM3 [97], IL1B [98], SLC6A14 [99], FPR1 [100], NOS2 [101], CHI3L1 [102], TGM2 [103], MUC4 [104], TREM1 [105], WNT5A [106], HGF (hepatocyte growth factor) [107], CXCL9 [108], GBP1 [109], S100A11 [110], ADM (adrenomedullin) [111], CXCL11 [112], CXCL10 [113], LILRB2 [114], GDF15 [115], IL1RN [116] STAT1 [117], SLAMF7 [105], CYP27B1 [118], NETO2 [119], TFPI2 [120], ZC3H12A [121], MMP1 [122], CSF3 [123], SOCS3 [124], TLR8 [125], HTRA3 [126], CEBPB (CCAAT enhancer binding protein beta) [127], CD55 [128], CXCR2 [129], CCL28 [130], CBR3 [131], CCL3 [132], FCGR2A [48], ACSL1 [133], CCL2 [134], SOD2 [135], CD14 [136], IGFBP2 [137], CD274 [138], DERL3 [139], SERPINE1 [140], IDO1 [141], PDK...…”
Section: Discussionmentioning
confidence: 99%